Study on Acoustic Emission and Damage Mechanical Properties of Freeze-Thaw Sandstone under Uniaxial Compression. (30th July 2022) - Liang, Bo; Yang, Gengshe; Yu, Jinjie
Abstract : The damage strength of freeze-thaw rock provides an important reference for stability evaluations used during rock engineering in cold regions. In this paper, real-time acoustic emission tests of saturated sandstone are performed after various freeze-thaw cycles to study the uniaxial compressive strength and deformation characteristics of the resulting materials. The macro-meso damage evolution law of loaded sandstone is studied under the action of freeze-thaw cycles. The results show the following: (1) The saturated water absorption of sandstone increases, the peak strength and elastic modulus loss rates of sandstone increase linearly, and the frost resistance of the rock decreases with the number of freeze-thaw cycles. The sandstone failure mode gradually shifts from splitting failure to complex splitting shear failure of the failure surface. (2) If fewer than 10 freeze-thaw cycles are applied, the ring count signals at the compaction stage and after the peak strength is reached are extremely weak under a uniaxial compression load. With additional freeze-thaw cycles, damage inside the rock accumulates gradually, and the ring count signal appears during the rock compaction stage, fluctuates up and down, and continues until the peak strength is reached. When the compressive strength reaches its peak, the ring count intensity signal increases suddenly, and the frequency is high. After the strength reaches its peak, the acoustic emission signal shows that the rock sample still has some residual strength. As the number of freeze-thaw cycles increases, the cumulative ring count of sandstone gradually changes from the jumping stage to gradual growth. The acoustic emission characteristic parameters and ring count reflect damage to and expansion of freeze-thaw sandstone. (3) The cumulative extent of rock damage reaches the threshold value under loading and increases linearly until the rock is destroyed. When more freeze-thaw cycles are used, the time required for the rock to reach this threshold value is shorter, and the time required for sandstone damage is reduced gradually. These results provide a reference for the study of freeze-thaw damage and rock stability in cold regions.